2003
DOI: 10.1002/ejsp.163
|View full text |Cite
|
Sign up to set email alerts
|

Perspective taking and prejudice reduction: the mediational role of empathy arousal and situational attributions

Abstract: This research was designed to examine whether perspective taking promotes improved intergroup attitudes regardless of the extent that stereotypic perceptions of outgroups are endorsed, as well as examining the mechanisms (attributional or empathy related) by which perspective taking motivates improved intergroup attitudes. Participants were presented with an interview segment where an African American interviewee discussed the difficulties experienced as a result of his membership in a negatively stereotyped g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
425
4
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(485 citation statements)
references
References 31 publications
37
425
4
8
Order By: Relevance
“…First, we replicated the findings from Experiments 1 and 2 using a different measure of automatic evaluations. Second, we replicated previous research showing that perspective taking leads to more positive deliberate evaluations of African Americans as a group (e.g., Vescio et al, 2003). Third, we demonstrated that changes in automatic evaluations mediated changes in deliberate evaluations.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…First, we replicated the findings from Experiments 1 and 2 using a different measure of automatic evaluations. Second, we replicated previous research showing that perspective taking leads to more positive deliberate evaluations of African Americans as a group (e.g., Vescio et al, 2003). Third, we demonstrated that changes in automatic evaluations mediated changes in deliberate evaluations.…”
Section: Resultssupporting
confidence: 87%
“…These findings are con- sistent with our prediction-derived from the attitudes literature (Neumann et al, 2003)-that the changes in automatic interracial evaluations found in Experiments 1-3 should translate to stronger approach reactions and weaker avoidance reactions to Black Americans. Furthermore, the effects of perspective taking were specific to Black targets (see also Batson, Polycarpou, et al, 1997;Shih et al, 2009;Vescio et al, 2003), suggesting that the results of the first three experiments are likely to reflect increased positivity toward Black Americans rather than increased negativity toward White Americans. Thus far, we have primarily examined the impact of perspective taking on intrapersonal dependent variables, albeit ones that should theoretically have noteworthy interpersonal consequences.…”
Section: Seating Distancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the benefits of shared experiences tend to generalize beyond the individual with whom one shares this experience, leading to a reduction in prejudice and stereotyping of this person's group as a whole (e.g., Batson, Early, & Salvarani, 1997;Broockman & Kalla, 2016;Galinsky & Ku, 2004;Galinsky & Moskowitz, 2000;Vescio, Sechrist, & Paolucci, 2003).…”
Section: Turning Toward Each Other Across Different Identity Dimensiomentioning
confidence: 99%
“…Other research has demonstrated that perspective taking can decrease the actor-observer bias by increasing observers' situational attributions for actors' behavior, particularly for negative events APPRAISAL AND EMPATHY 46 (Betancourt, 1990;Galper, 1976;Gould & Sigall, 1977;Storms, 1973;Vescio, Sechrist, & Paolucci, 2003). When perspective taking manipulations are employed in typical compassion research paradigms, they might increase compassion by directing subjects' attention to situational causes of a target's misfortune.…”
Section: Implications Of the Theory For Perspective Takingmentioning
confidence: 99%